FERROPTOSIS AND ITS CLINICAL SIGNIFICANCE - Agić, Danijela; Vranješ, Marijana; Dragičević Jojkić, Marina; El Farra, Amir; Urošević, Ivana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Ferroptosis, mentioned as such for the first time in 2012 by Dixon et al., is an iron-dependent type of cell death that occurs in the presence of lipid peroxides. The mechanism of the process and the signaling pathways involved in it differ from the previously known apoptosis, necrosis, and autophagy. An inflammatory reaction also occurs, which further distinguishes this type of cell death from apoptosis. Ferrostatin inhibits this process. Methods: A review of the literature obtained by searching the Medline database was performed, with a special focus on studies concerned with the importance of ferroptosis in clinical medicine, primarily hematology. Results: Iron metabolism in malignant and healthy cells differs. Malignant cells tolerate oxidative stress well and avoid ferroptosis. According to literature data, various tested agents stimulate ferroptosis and thus become possible therapeutic agents. Some genes linked to iron metabolism have shown prognostic significance in patients with diffuse large B-cell lymphoma. Conclusion: The discovery of new mechanisms of cell death and the signaling pathways involved in this process leads to potentially new target therapy. Although promising, these results require validation through further research.